2017
DOI: 10.1075/sibil.52.04bro
|View full text |Cite
|
Sign up to set email alerts
|

Semantic prediction in monolingual and bilingual children

Abstract: One of the mechanisms responsible for the fast recognition of spoken language is prediction. This study examined whether 4–5 year old monolingual children differ from bilingual children in predicting the upcoming noun on the basis of the lexical semantics of the verb. In an eye-tracking task, we presented visual displays with two objects (e.g. cake, tree) while presenting semantically constraining (e.g. The boy eats the big cake) or neutral sentences (e.g. The boy sees the big cake). Results showed that both g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 40 publications
1
11
0
Order By: Relevance
“…Our Dutch data demonstrated a semantic prediction effect over time for all our age groups (see also Brouwer et al, 2017). This replicates previous work with children and adults with different native languages such as English (e.g., Altmann & Kamide, 1999) and German (Mani & Huettig, 2012).…”
Section: Discussionsupporting
confidence: 89%
“…Our Dutch data demonstrated a semantic prediction effect over time for all our age groups (see also Brouwer et al, 2017). This replicates previous work with children and adults with different native languages such as English (e.g., Altmann & Kamide, 1999) and German (Mani & Huettig, 2012).…”
Section: Discussionsupporting
confidence: 89%
“…In fact, some evidence in support of this prediction has been reported in previous studies. Although the studies of which we are aware have relied on group comparisons, rather than individual-level measures, a body of work has demonstrated that bilinguals and L2 learners use morphosyntactic cues during processing to a reduced degree compared to monolingual counterparts [66][67][68][69][70], while at least one previous study has demonstrated evidence that bilinguals exhibit increased semantic prediction relative to monolingual counterparts [71]. Of course, more research is needed to understand the relationship between semantic and syntactic processing in later-learned languages, particularly regarding how this relationship is modulated by continuous factors at the level of the individual.…”
Section: Discussionmentioning
confidence: 99%
“…The children heard sentences such as The boy eats/sees the big cake while being presented with visual stimuli depicting two objects, where only one was edible. Brouwer et al (2017) found that all the children (4- and 5-year-old monolinguals and bilinguals) predicted upcoming noun arguments based on the semantics of verbs. The researchers also found that the 4-year-old bilinguals predicted faster than their monolingual peers.…”
Section: Introductionmentioning
confidence: 90%
“…Hence, investigation of language prediction in children who acquire more than one language could potentially shed more light on the factors contributing to its development. Studies investigating prediction in language comprehension in bilingual children are few ( Brouwer et al, 2017 ; Lemmerth and Hopp, 2019 ; Meir et al, 2020 ), and to the best of our knowledge, no studies have focused on this ability in bilingual toddlers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation